Answer:
Explanation:
Inserting the coordinates of the center (3, 4) into the standard equation of a circle with center at (h, k) and radius r, we get:
(x - 3)^2 + (y - 4)^2 = r^2
Next, we substitute 2 for x, 6 for y and solve the resulting equation for r^2:
(2 - 3)^2 + (6 - 4)^2 = r^2, or
1 + 4 = r^2.
Thus, the radius is √5. Subbing this result into the equation found above, (x - 3)^2 + (y - 4)^2 = r^2, we get:
(x - 3)^2 + (y - 4)^2 = (√5)^2 = 5, which matches the last of the four possible answer choices.